2016
DOI: 10.1245/s10434-016-5145-z
|View full text |Cite
|
Sign up to set email alerts
|

Is Sentinel Lymph Node Biopsy Indicated at Completion Mastectomy for Ductal Carcinoma In Situ?

Abstract: Background Sentinel lymph node biopsy (SLNB) is recommended when mastectomy is performed for ductal carcinoma in situ (DCIS). The role of SLNB for women with DCIS who undergo mastectomy following ≥1 attempts at breast-conserving surgery (BCS) is uncertain. We examined the upgrade rate and SLNB yield in women who converted to mastectomy after ≥1 attempts at BCS for DCIS. Methods All patients who underwent ≥1 attempts at BCS prior to conversion to mastectomy with SLNB for DCIS were identified. Margin status as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
3
8
1
Order By: Relevance
“…We found the upstage rate to invasive carcinoma to be 29%. This is consistent with the reported 8%‐40% upstage rate and corresponds with Brennan et al's meta‐analysis which found 26% (95% CI: 23%‐30%) of patients with an initial diagnosis of DCIS on PCB had invasive disease on final pathology. In our study, the rate of SLN positivity among these upstaged patients was small but clinically significant (10%).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…We found the upstage rate to invasive carcinoma to be 29%. This is consistent with the reported 8%‐40% upstage rate and corresponds with Brennan et al's meta‐analysis which found 26% (95% CI: 23%‐30%) of patients with an initial diagnosis of DCIS on PCB had invasive disease on final pathology. In our study, the rate of SLN positivity among these upstaged patients was small but clinically significant (10%).…”
Section: Resultssupporting
confidence: 91%
“…These factors were palpability, extent of disease on imaging larger than 1.20 cm and mass on pre‐op imaging. Other studies have demonstrated the utility of these preoperative markers of upstage risk . Multicentricity, patient reported symptoms and the presence of necrosis have also been reported as predictive factors; our study did not corroborate the significance of these additional findings.…”
Section: Resultscontrasting
confidence: 86%
See 2 more Smart Citations
“…A second explanation is that surgeons may be concerned about finding an occult primary invasive cancer in the mastectomy specimen and are therefore performing a prophylactic sentinel lymph node biopsy as is the standard recommendation for patients undergoing mastectomy for ductal carcinoma in situ (DCIS). 1517 Another explanation is that patients are taken to the operating room with a presumed diagnosis of adenocarcinoma and undergo lymph node sampling. It is only on final pathology that the diagnosis of phyllodes is made.…”
Section: Discussionmentioning
confidence: 99%